Label-free high frame rate imaging of circulating blood clots using a dual modal ultrasound and photoacoustic system - Das, Dhiman (2021)
Deep vein thrombosis (DVT) is a disorder when a blood clot (thrombus) is formed in one of the deep veins. These clots detach from the original sites and circulate in the blood stream at high velocities. Diagnosing these blood clots at an early stage is necessary to decide the treatment strategy. For label-free, in vivo and real-time detection, high framerate photoacoustic imaging can be used. In this work, a dual modal clinical ultrasound (US) and photoacoustic (PA) system is used for the high framerate PA imaging of circulating blood clots in blood at linear velocities up to 107 cm/sec. Blood clot had 1.4 times higher signal-to-noise ratio (SNR) in the static mode and 1.3 times higher SNR compared to blood PA signal in the flow experiments. This work demonstrates that fast-moving circulating blood clots are easy to recognize against the background PA signal and may aid in early diagnosis.